(untitled) (Journal of Health Sciences, 2017)
Introduction: Osteoporosis is a skeletal system disease characterized by decline of bone mass and deterioration of bone microarchitecture, which leads to increased bone fragility and, consequently, a greater risk of fractures. Postmenopausal osteoporosis generally occurs between 51 and 75 years of age following ovarian failure. Our aim was to investigate if specific lifestyle habits, i.e., smoking cigarettes and physical activity, as well as the intake of dietary supplements, affect bone mineral density (BMD) in postmenopausal women.Methods: Ultrasound (US) and dual energy X-ray absorptiometry (DEXA) data, obtained between 2008 and 2009 year, were retrospectively reviewed for 150 women in postmenopause, 50-65 years old, who live in Sarajevo Canton. The women were classified into two groups: Group A (75 postmenopausal women who underwent US of the left heel bone); control group B (75 postmenopausal women who underwent US of the left heel bone and had a DEXA scan of the lumbar spine and left hip).Results: The study included 150 women with the average age of 55.39 years. In the total sample, 24.7% of women took calcium and vitamin D supplements, and no statistically significant difference was observed between the groups. In the total sample, the prevalence of osteoporosis was significantly different between smokers and nonsmokers; i.e., osteoporosis was more frequent in women who smoked cigarettes. On average, women in both groups reported low physical activity; the difference was not statistically significant.Conclusions: Menopause is a known risk for osteoporosis. Our results showed that the length of menopause is closely associated with osteoporosis occurrence.